Exploiting an oil palm EST database for the development of gene-derived SSR markers and their exploitation for assessment of genetic diversity. - Singh, Rajinder; Mohd Zaki, Noorhariza; Ngoot-Chin , Ting; Rosli, Rozana; Soon-Guan, Tan; Eng-Ti , Leslie Low; Ithnin, Maizura; Suan-Choo , Cheah (Institute of Molecular Biology, Slovak Academy of Sciences, 2008)
A total of 5,521 expressed sequence tags (ESTs) from oil palm were used to search for type and frequency of simple sequence repeat (SSR) markers. Dimeric repeat motifs appeared to be the most abundant, followed by trinucleotide repeats. Redundancy was eliminated in the original EST set, resulting in 145 SSRs in 136 unique ESTs (114 singletons and 22 clusters). Primers were designed for 94 (69.1%) of the unique ESTs (consisting of 14 consensus and 80 singletons). Primers for 10 EST-SSRs were developed and used to evaluate the genetic diversity of 76 accessions of oil palm originating from seven countries in Africa, and the standard Deli dura population. The average number of observed and effective alleles was 2.56 and 1.84, respectively. The EST-SSR markers were found to be polymorphic with a mean polymorphic information content value of 0.53. Genetic differentiation (F ST) among the populations studied was 0.2492 indicating high level of genetic divergence. Moreover, the UPGMA (unweighted pair-group method with arithmetic mean) analysis revealed a strong association between genetic distance and geographic location of the populations studied. The germplasm materials exhibited higher diversity than Deli dura, indicating their potential usefulness in oil palm improvement programmes. The study also revealed that the populations from Nigeria, Congo and Cameroon showed the highest diversity among the germplasm evaluated in this study. The EST-SSRs further demonstrated their worth as a new source of polymorphic markers for phylogenetic analysis, since a high percentage of the markers showed transferability across species and palm taxa.